Investigation of precipitation and temperature trends using classical and innovative approaches with corresponding frequencies in Antalya Basin, Türkiye - Ercan, Cansu; Abu Arra, Ahmad; Sisman, Eyup (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The adverse impacts of climate change have increased significantly, which calls for studying trends in meteorological and hydrological variables to enhance our standing of its effects and analyze them in depth, which is of great importance. This research aims to apply the newly proposed Frequency-Innovative Trend Analysis (F-ITA) methodology along with the classical trend methods, including Mann-Kendall (MK) and Sen's Slope (SS), to investigate the actual trends, magnitude, and direction of trends with their spatial and temporal changes over Antalya basin, T & uuml;rkiye, using monthly precipitation and temperature data. Also, equal intervals for classification and corresponding frequencies with the enhanced visualization and evaluation of F-ITA methodology are introduced in this research as a novel approach. For precipitation, the F-ITA graphs indicated no trend or a decreasing trend over the Antalya Basin; for example, the A. Havaliman & imath; station showed a decreasing trend in the high and very high subclassifications, with frequencies declining from 7.415 % to 9.88 %-4.01 % and 8.33 %, respectively. Also, the temperature trend in the Antalya Basin increased with corresponding frequencies, like the Alanya station, where the very high subclassification frequency increased significantly from 21.6 % to 33.95 %. The comparison between slopes from SS and ITA methodologies revealed differences and similarities, largely attributed to the methodological differences between the two approaches. The results of this research are highly important in the context of climate change adaptation strategies and can be utilized in sustainable water resource management and improve the agricultural sector in the study area.
Keywords: Climate change; Time series; Water resources management; Mann-Kendall; Innovative trend analysis (ITA); Trend analysis; NONPARAMETRIC-TESTS; RAINFALL; HOMOGENEITY; CATCHMENT; INDEXES; Geology; Meteorology & Atmospheric Sciences; Water Resources